A Legal Analysis of Debt Relations from the Perspective of the Qur’an and Indonesian Positive Law - Adi Prihasmoro; Helmi Hidayat (Indonesian Journal of Law and Policy Studies, 2025)
This study examines debt settlement practices in society from the perspectives of the Qur’an and Indonesian positive law. It employs a literature review and statutory approach, with qualitative analysis presented descriptively. The findings reveal that debt is comprehensively regulated in QS. Al-Baqarah (2:282), known as the mudayanah verse, which situates debt within commercial transactions, prohibits usury, and encourages almsgiving as part of broader muamalah (civil relations). Debt should not be narrowly understood as mere borrowing, but as encompassing all legal engagements arising from agreements, transactions, and reciprocal relations. Normatively, debt constitutes an obligation that must be fulfilled by the debtor, even taking priority over inheritance distribution upon death. However, in practice, debt relations risk leading to usury. Therefore, the Qur’an provides ethical guidance, including granting repayment extensions or partial/complete debt relief for debtors facing hardship. Overall, debt regulation reflects a balance between compassion and responsibility in managing wealth, serving both social harmony and spiritual objectives. These principles remain relevant and can be implemented by Indonesian Muslims in alignment with the existing legal framework